Effect of different cooking methods on flavor compounds of Chinese traditional condiment Wuxiang powder. Issue 3 (30th January 2022) - Bi, Jicai; Li, Yang; Lin, Zeyuan; Yang, Zhen; Chen, Fusheng; Liu, Sixin; Li, Congfa
Abstract: The Wuxiang powder is a Chinese traditional condiment with a strong aroma and flavor. Moreover, it is suitable for dishes prepared using several cooking methods. Gas chromatography–ion mobility spectrometry was used to analyze the changes in the flavor of the original Wuxiang powder, the air‐fried Wuxiang powder and the stewed Wuxiang powder. A total of 49 volatile compounds were studied, including 17 aldehydes, 9 alkenes, 9 esters, 7 alcohols, 2 ethers, 2 furans, 1 acid, 1 ketone and 1 phenol. The contents of aldehydes, hydrocarbons, esters and alcohols were higher than others. The principal component analysis elucidated significant differences in the aroma among different cooking methods of the Wuxiang powder. According to the relative odor activity value, the major flavor compounds that contributed to the difference in the aroma among different cooking methods were (Z, Z)‐2, 4‐decadienal, anethole, decanal, 3‐methylbutanal, β‐caryophyllene, α‐pinene, linalool, eugenol, octanal, heptanal, and hexanal. Practical applications: The Wuxiang powder is one of the most common commercial condiments and is known for its excellent flavor and nutritional value. It is often used in frying, roasting, boiling, cold mixing, and other cooking methods. The volatile components in the Wuxiang powder undergo changes due to different cooking methods. However, the literature comparing the volatile compounds in different cooking methods is little. We believe that this research could provide the basis data for Wuxiang flavor products.